The Influence of Compensation Towards Employee Productivity at PT. Citra Jaya Nusantara Pekanbaru - Hengky Kosasih; Susanto; Robin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
PT. Citra Jaya Nusantara is company that run a business in property sector. This company has run its business in Pekanbaru for around two years. The main business is building shophouses. Employee productivity relates positively to the compensation system design of an enterprise. Since this is the key indicator of the selection of pay strategies, it should be highly valued. Compensation strategy is seen as one of the most important strategies in management function as it influences the productivity and growth of an organization. The objective of this research is to know the influence of compensation toward employee productivity at PT. Citra Jaya Nusantara Pekanbaru. Based on statistical calculation and analysis, the data is highly valid and the questionnaire is reliable. The Pearson correlation coefficient is 0,75 and the determination is 56%. This means that there are high and positive relation between compensation and employee productivity. Compensation influences employee productivity only for 56%, the other factors influence productivity for 44%. The linear regression equation of this variable is Y = 7,09 + 0,69X. The Zcount of this skripsi is 4,1983 and Ztable 1,96. Since Zcount > Ztable, hence Ha is accepted. This means that compensation influences employee productivity at PT. Citra Jaya Nusantara Pekanbaru.